Enabling Technology for Supramolecular Chemistry - Ollerton, Katie; Greenaway, Rebecca L.; Slater, Anna G. (Frontiers in Chemistry, 2021)
Supramolecular materials – materials that exploit non-covalent interactions – are increasing in structural complexity, selectivity, function, stability, and scalability, but their use in applications has been comparatively limited. In this Minireview, we summarize the opportunities presented by enabling technology – flow chemistry, high-throughput screening, and automation – to wield greater control over the processes in supramolecular chemistry and accelerate the discovery and use of self-assembled systems. Finally, we give an outlook for how these tools could transform the future of the field.